Pengaruh Pengembangan Karir, Kepuasan Kerja, Dan Kompetensi Terhadap Kinerja Pegawai Badan Pemerintah Kota Malang - Mulida Noer Chamila; Pardiman Pardiman; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze and determine the influence of career development, job satisfaction, and competence on employee performance at the Malang City Government Agencies, both simultaneously and partially. The type of research used is quantitative research with a descriptive approach. The population in this study includes all 159 employees in five agencies of the Malang City Government, with a sample of 62 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression methods with the help of SPSS software. The results showed that simultaneously, career development, job satisfaction, and competence significantly influence employee performance. Partially, career development and competence are proven to have a positive and significant effect on employee performance. However, the job satisfaction variable was found to have no significant partial effect on employee performance at the Malang City Government Agencies. The Adjusted R Square value of 0.429 indicates that 42.9% of the variation in employee performance is influenced by these three independent variables, while the remaining is influenced by other factors outside this study. Keywords: Career Development, Job Satisfaction, Competence, Employee Performance, Government Agency, Human Resources.